Is breast cancer surgery safely performed in patients receiving antithrombotic therapy? - Emoto Norio (Innovative Surgical Science, 2017)
The aim of the study was to assess the safety of surgery for breast cancer in patients with antithrombotic therapy (ATT), including antiplatelet therapy (APT) and anticoagulation therapy (ACT) for thromboembolic risks.